Biology and Control of Coast Cockspur in Sugarcane - Dennis Calvin Odero; Ron Rice; Les Baucum (EDIS)
Coast cockspur is a relative of barnyardgrass that is native to North America. In South Florida, coast cockspur typically begins to infest sugarcane during the onset of rainfall in late spring. This 2-page fact sheet was written by Dennis Calvin Odero, Ron Rice, and Les Baucum, and published by the UF Department of Agronomy, January 2013.